The usefulness of published annual reports to individual investors in Singapore - Chua, Siew Hwee (2014)
The relaxation of the use of CPF savings for share purchase and the ready availability of financing in the application of new share issues have led to more investing in shares. According to a report in The Straits Times, Life!, December 1993, about 1.45 million Singaporeans now own shares -- compared to 254,832 in 1990, making Singapore the world's Number One share-owing nation on a per capita basis.